A Review on Multifunctional Polymer–MXene Hybrid Materials for Electronic Applications - Fatemeh Morshedi Dehaghi; Mohammad Aberoumand; Uttandaraman Sundararaj (Molecules)
MXenes, a family of two-dimensional (2D) transition metal carbides, carbonitrides, and nitrides, have emerged as a promising class of nanomaterials for interdisciplinary applications due to their unique physiochemical properties. The large surface area, excellent electrical conductivity, superior mechanical properties, and abundant possible functional groups make this layered nanomaterial an ideal candidate for multifunctional hybrid materials for electronic applications. This review highlights recent progress in MXene-based hybrid materials, focusing on their electrical, dielectric, and electromagnetic interference (EMI) shielding properties, with an emphasis on the development of multifunctionality required for advanced electronic devices. The review explores the multifunctional nature of MXene-based polymer nanocomposites and hybrid materials, covering the coexistence of a diverse range of properties, including sensory capabilities, electromagnetic interference shielding, energy storage, and the Joule heating phenomenon. Finally, the future outlook and key challenges are summarized, offering insights to guide future research aimed at improving the performance and functionality of MXene–polymer nanocomposites.